Testing the benefits of early vessel evolution. (28th June 2019) - Roddy, Adam B
Abstract : This article comments on: Trueba S, Delzon S, Isnard S, and Lens F . 2019. Similar hydraulic efficiency and safety across vesselless angiosperms and vessel-bearing species with scalariform perforation plates. Journal of Experimental Botany 70, 3227–3240.